The relationship between favorable organizational climate and organizational commitment and occupational violence among education teachers in Shiraz - Namjoo, Farhad; Namjoo, Kayhan; Motaghed, Aghil; Basiri, Ali; Khoshbayan, Amirali; Lyaghat, Ehsan (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2022)
Background and purpose: optimal and desirable education can be considered one of the basic elements of every society, and teachers, as the guardians of this matter, are considered one of the most important factors in advancing the goals of education. Any society's survival, durability, and progress depend on the quality of its education. Therefore, this research aimed to explain the relationship between favorable organizational climate, organizational commitment and occupational violence. Methodology: The research design was descriptive and correlational. The research's statistical population was comprised of all the teachers working in education in district 2 of Shiraz city. Among the statistical population, 169 people were selected and studied by purposeful sampling. In order to collect data, questionnaires on the psychological climate (1991), organizational commitment (1990), and occupational violence (2013). After collecting and extracting data, participants' scores were analyzed using Pearson's correlation and multiple and multivariable linear regression, and statistical software (SPSS). Results: The results showed a positive relationship between organizational climate and organizational commitment and a significant negative relationship between organizational climate and occupational violence. Also, there is a significant correlation between the subscales of independence, cohesion, trust, pressure, support, appreciation, fairness, and innovation with organizational commitment and occupational violence. Also, the results showed that favorable organizational climate and organizational commitment are able to predict occupational violence. Conclusion: The research results confirm the existence of a relationship between the psychology governing the organization and violence and job commitment in teachers. Therefore, a favorable psychological climate increases the efficiency, commitment, and performance of employees in the organization.